The Effect of Cognitive Behavioral Therapy (CBT) Based Group Counseling on Improving Students’ Career Decision Making - Herlina Murni Sari; Kus Hendar; Meita Sari (Universitas Islam Balitar, 2026)
Madrasah Aliyah Takhassus Al-Qur’an Al Falahiyah was established in 2018 to enhance the quality of Islamic education by integrating general academic knowledge with in-depth Qur’anic studies. Under the Al Falahiyah Islamic Boarding School Foundation, the institution is committed to nurturing a Qur’anic generation that is academically accomplished, morally upright, and globally competitive. This study aims to examine the effect of group counseling using a Cognitive Behavioral Therapy (CBT) approach on improving career decision-making among twelfth-grade students. The research employs a quantitative approach with a quasi-experimental one-group pretest–posttest design. The sample consists of 30 students selected through purposive sampling, specifically those experiencing uncertainty in making career decisions. Data were collected using a Likert-scale questionnaire adapted from the Career Decision-Making Difficulties Questionnaire (CDDQ) and analyzed using descriptive and inferential statistics with SPSS. The results show an increase in the mean career decision-making scores from pretest to posttest. Prerequisite tests confirmed that the data were normally distributed and homogeneous. The paired-samples t-test yielded a significance value of 0.018 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. These findings suggest that CBT-based group counseling is effective in enhancing students’ career decision-making by fostering more rational thinking, increasing self-confidence, and strengthening their ability to make realistic and well-informed career choices.